Bioinformatics tools to Predict N-myristoylation Site a Comparison Study - Arifin, Muhammad Zainul; Parikesit, Arli A. (Indonesia International Institute for Life Sciences, 2019)
Protein N-myristoylation is the covalent attachment of myrstate, via an amide bond, to the N-terminal glycine residue of a nascent polypeptide assisted by myristol-CoA protein: N-myristoltransferases (NMT). PROSITE motif describes 5 amino acid after glycine site that would give rise to myristoylation site. However, applied to whole database extract, this motif give too many false postive results. Therefore 2 new tools were developed for N-myristoylation prediction.Taking physical properties into consideration inceases prediction scores greatly. However, these algorithms still cannot predict myristoylated site correctly 100% of the time due to limited understanding of the real mechanims underlying N-myristoylation